2020
DOI: 10.1088/1742-6596/1521/4/042077
|View full text |Cite
|
Sign up to set email alerts
|

Developing 22nd century skills through the integration of STEAM into smoke absorber project

Abstract: This study aimed to develop 22nd century skills through the integration of STEAM (Science, Technology, Engineering, Art, and Mathematics) project in chemistry learning. The study involved the thirty-three students of 11 year. The STEAM integration was implemented in the teaching of colloidal system through a project-based learning. The study employed qualitative approach to explore the integration of STEAM in chemistry and students’ 22nd century skills development. Data were collected through classroom observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…A STEAM approach can develop students' critical thinking skills, creativity, collaboration, communication skills, and awareness (5C) of environmental problems. It can also develop students' information, media, and technology skills such as operating various learning media platforms, using virtual classes and using various software to edit images or videos (Ridwan, Rahmawati, Mardiah & Rifai, 2020).…”
Section: ) Testmentioning
confidence: 99%
“…A STEAM approach can develop students' critical thinking skills, creativity, collaboration, communication skills, and awareness (5C) of environmental problems. It can also develop students' information, media, and technology skills such as operating various learning media platforms, using virtual classes and using various software to edit images or videos (Ridwan, Rahmawati, Mardiah & Rifai, 2020).…”
Section: ) Testmentioning
confidence: 99%
“…Based on the research of Pratiwi et al [3], E-Books can be used in learning with a STEM approach. STEM learning can shape students to have critical, collaborative, creative, and communicative thinking skills [13,14]. According to Maynastiti et al [15], using E-Books in learning can improve students' physics problem-solving skills because it supports physics learning, which is needed by the media to explain existing physical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies results are not consistent on whether STEAM course improves the critical thinking of students. For example, Ridwan et al (2020) implemented a STEAM course based on a smoke absorber project in a high school chemistry course. Through simple analysis of online discussion texts, the study found that STEAM courses can promote the development of the critical thinking of students (Ridwan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ridwan et al (2020) implemented a STEAM course based on a smoke absorber project in a high school chemistry course. Through simple analysis of online discussion texts, the study found that STEAM courses can promote the development of the critical thinking of students (Ridwan et al, 2020). However, other researchers have found a different result.…”
Section: Introductionmentioning
confidence: 99%